HUBUNGAN KELAS KESESUAIAN LAHAN TANAMAN TEBU DENGAN RENDEMEN DAN KEUNTUNGAN - Dwi Asnawi Nurhananto; Bambang Siswanto (BUANA SAINS, 2016)
Aims of this research is to evaluate relation land suitable class by using class criterion according to different farm to production, rendemen and advantage of sugarcane crop. Criterion of land suitability perceived to cover climate, condition of root, retention of nutrion, availibility of virgin, condition of surface of farm with using two criterion is Djaenuddin et al. (2003) and FAO (1983). The result indicate that assessment of land sustainability use criterion of Djaenudin et al. ( 2003) yielded by correspondence among physical class, class produce and class of rendemen equal to 33,3 gratuity. While advantage class counted 41,6 gratuity good match for physical class but jar with with class produce and also rendemen. Accumulatively advantage class tend to compared to lower of physical class, class produce and advantage class. Assessment of land suitability use criterion of FAO (1983) at yielded by correspondence among physical class, class produce and class of rendemen equal to 8,3 gratuity. Advantage class counted 66,6 gratuity good match for physical class but jar with with class produce and also rendemen. Incompatible all result of assessment of class according to sugar cane crop farm among physical class, production class, class of rendemen advantage class and at set of usage of farm because of difference in stipulating of criterion according to and decision making in classification according to farm. Usage of farm quality as factor influencing and production of rendemen not yet complete included as farm criterion at Djaenuddin et al. ( 2003) and also FAO ( 1983)